Ultrasonic pulse velocity (upv) in concrete under compression:a study on the effect of orientation of measurement - Chia, F.J (Universiti Malaysia Sarawak (UNIMAS), 2004)
This research project describes the preliminary findings on the orientation of measurements; by determining the ultrasonic pulse velocity in the concrete under compressive stresses. The laboratory investigation was carried out to analyze the changes of transit time corresponding to the effect of concrete ages, grades and the size ratio of prisms.